ANALISIS BUDAYA ORGANISASI DALAM UPAYA MENINGKATKAN MOTIVASI KARYAWAN PT. RAJAWALI NUSANTARA INDONESIA (PERSERO) CABANG MEDAN - PAWER PANJAITAN (LP2MTBM MAKARIOZ, 2019)
Organizational culture is about the subjective aspects of what happens within a company, refers to abstractions such as values and norms that cover all or parts of a business. Pg this may not be defined, discussed or even noticed. But culture can have influence on one's behavior at work. Organizational culture is very much needed by each companies that need to always be developed and adapted to changing organizational environments. The organizational environment consists of human resources with backgrounds and levels different. Thus, changes in organizational culture are carried out first change the mindset of all human resources in the organization. Organizational culture is a value that guides human resources to deal with both external and internal problems and at the same time attempts to adjust integration into the organization so that each member of the organization must understand the values that exist, how to act and behave. Thus the organizational culture makes organizational members to focus on achieving organizational goals have a different culture, because they have different cultural backgrounds, but all the differences will be merged into one in a culture that is organizational culture, to become a group that collaborates in achieve organizational goals as previously agreed upon, but in the process it is also possible that there are individuals who can accept it and also who cannot accept it, which may conflict with their culture.